Ionizing Radiation in Glioblastoma Initiating Cells - Rivera, Maricruz; Sukhdeo, Kumar; Yu, Jennifer S. (Frontiers in Oncology, 2013)
Glioblastoma is the most common primary malignant brain tumor in adults with a median survival of 12-15 months with treatment consisting of surgical resection followed by ionizing radiation (IR) and chemotherapy. Even aggressive treatment is often palliative due to near universal recurrence. Therapeutic resistance has been linked to a subpopulation of GBM cells with stem-cell like properties termed glioblastoma initiating cells (GICs). Recent efforts have focused on elucidating resistance mechanisms activated in GICs in response to IR. Among these, GICs preferentially activate the DNA damage response (DDR) to result in a faster rate of double-strand break (DSB) repair induced by IR as compared to the bulk tumor cells. IR also activates NOTCH and the hepatic growth factor (HGF) receptor, c-MET, signaling cascades that play critical roles in promoting proliferation, invasion, and resistance to apoptosis. These pathways are preferentially activated in GICs and represent targets for pharmacologic intervention. While IR provides the benefit of improved survival, it paradoxically promotes selection of more malignant cellular phenotypes of glioblastoma. As reviewed here, finding effective combinations of radiation and molecular inhibitors to target GICs and non-GICs is essential for the development of more effective therapies.